Ambedkar on law, constitution, and social justice - Shabbir, Mohd (Rawat Publications, 2005)
he book deals with diverse burning issues which are directly related to individuals, society, state, law and constitution revolving round the concept of social justice. It focuses on poverty jurisprudence highlighting the problems of the scheduled castes, backward segments, weaker sections and minorities searching the ideal solutions of their problems, and also suggesting ways and means for tackling them successfully. The central theme of the book examines different problematic issues from the touchstone of Ambedkar's humanistic philosophy championing the cause of downtrodden. This book has potentiality of enriching human rights jurisprudence. Indeed, this is a potent addition to existing knowledge of law, constitution and social justice